ANALISIS DAMPAK INDUSTRI MIKRO DAN KECIL TERHADAP PERTUMBUHAN EKONOMI INDONESIA DENGAN PENDEKATAN EKONOMETRIK REGRESI SPASIAL PADA DATA PANEL - Ameylia Daniek Setiya Ningrum; Rizkha Arum Cantika; Ifan Surya Dwi Oktafianto; Aryogi Adi Saputra; Muhammad Farhan; Delonika Diah Ayu (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
One way to evaluate a country's economic condition is by examining the Gross Domestic Product (GDP) at the national level or the Gross Regional Domestic Product (GRDP) at the regional level. In Indonesia, the manufacturing industry is the largest contributor to GDP. Within this sector, micro and small-scale industries (MSIs) play a vital role. MSIs significantly drive economic development, with their impact varying across different geographical locations, thus influencing the GRDP of various regions. Therefore, it is essential to analyze GRDP with spatial considerations, examining how the MSI sector affects economic growth in Indonesia through spatial panel data regression. This study employs spatial models such as the Spatial Autoregressive Model (SAR) and the Spatial Error Model (SEM) with fixed effects to understand these dynamics. The research aims to identify and describe the MSI-related factors that affect economic growth in Indonesia's provinces. The findings indicate that the most suitable model is the Spatial Autoregressive Model Fixed Effect (SAR-FE). The study identifies two significant independent variables influencing economic growth: the number of micro and small-scale industries (X1) and inflation (X6). The results demonstrate that increases in these variables correlate with a decrease in the economic growth rate.